Emerging Limb Rehabilitation Therapy After Post-stroke Motor Recovery - Xiong, Fei; Liao, Xin; Xiao, Jie; Bai, Xin; Huang, Jiaqi; Zhang, Bi; Li, Fang; Li, Pengfei (Frontiers in Aging Neuroscience, 2022)
Stroke, including hemorrhagic and ischemic stroke, refers to the blood supply disorder in the local brain tissue for various reasons (aneurysm, occlusion, etc.). It leads to regional brain circulation imbalance, neurological complications, limb motor dysfunction, aphasia, and depression. As the second-leading cause of death worldwide, stroke poses a significant threat to human life characterized by high mortality, disability, and recurrence. Therefore, the clinician has to care about the symptoms of stroke patients in the acute stage and formulate an effective postoperative rehabilitation plan to facilitate the recovery in patients. We summarize a novel application and update of the rehabilitation therapy in limb motor rehabilitation of stroke patients to provide a potential future stroke rehabilitation strategy.